Acid-degradable magnolol-containing polymeric prodrug micelles for enhanced gastric cancer therapy - Dongshi Liang; Meiqian Yu; Shuaishuai Huang; Jinglin Wang; Zijin Xu; Daai Li; Zhongyu Li; Huamin Wang (Materials & Design, 2023)
Magnolol shows promise as an effective anti-tumor therapeutic agent. Nevertheless, the clinical application of this agent is constrained by its inherent water insolubility and diminished stability. In the present investigation, we have developed a new approach to address these limitations by creating an acid-responsive amphiphilic polymeric prodrug (PMag) that contains acetal bonds and magnolol, and can self-assemble into polymeric micelles (PMag-Ms) in aqueous solutions. We conducted in vitro release studies and observed that the micelles rapidly released magnolol at an acidic pH of 5.0, but only released minimal amounts of magnolol at a neutral pH of 7.4. In vitro investigations performed on gastric cancer cells elucidated that PMag-Ms selectively induced cell apoptosis and G1 phase cell cycle arrest, exhibiting higher efficacy than magnolol alone. Furthermore, in vivo studies confirmed that PMag-Ms exhibited superior inhibition of tumor growth, favorable biocompatibility with organs, increased accumulation in tumor tissues, and enhanced targeting efficiency compared to magnolol. Pharmacokinetic analysis also revealed that PMag-Ms had a longer half-life and extended duration of action in vivo. These results highlight the potential of the synthesized acid-degradable PMag-Ms as a promising therapeutic option for gastric cancer.